Expert advice from ResearchMatch volunteers: Recruitment Innovation Center use cases and innovation - Maeve Tischbein; Sarah K. Cook; Cathy Shyr; Katelyn Benhoff; Amna Baig; Kaysi Quarles; Leslie R. Boone; Loretta M. Byrne; Mariela Rodriguez; Terri Edwards; Consuelo H. Wilkins; Paul A. Harris (Journal of Clinical and Translational Science)
Involving participants in the design of clinical trials should improve the overall success of a study. For this to occur, streamlined mechanisms are needed to connect the populations potentially impacted by a given study or health topic with research teams in order to inform trial design in a meaningful and timely manner. To address this need, we developed an innovative mechanism called the “ResearchMatch Expert Advice Tool” that quickly obtains volunteer perspectives from populations with specific health conditions or lived experiences using the national recruitment registry, ResearchMatch. This tool does not ask volunteers to participate in the trial but allows for wider community feedback to be gathered and translated into actionable recommendations used to inform the study’s design. We describe early use cases that shaped the current Expert Advice Tool workflow, how results from this tool were incorporated and implemented by studies, and feedback from volunteers and study teams regarding the tool’s usefulness. Additionally, we present a set of lessons learned during the development of the Expert Advice Tool that can be used by other recruitment registries seeking to obtain volunteer feedback on study design and operations.